Synthesis, Thermal and Electrochemical Properties of Four New Bis Oxadiazole Copolymers Based on Azo Monomer - Juman A. Naser (Journal of Global Pharma Technology, 2016)
Four new copolymers were synthesized from reaction of bis acid monomer 3-((4-carboxyphenyl)diazenyl)-5-chloro-2-hydroxybenzoic acid with five diacidhydrazide in presence of poly phosphoric acid. The resulted monomers and copolymers have been characterized by FT-IR, 1H-NMR, 13C-NMR spectroscopy as well as EIMs technique. The number averages of molecular weights of the copolymers are between 4822 and 9144, and their polydispersity indexes are between 1.02 and 2.15. All the copolymers show good thermal stability with the temperatures higher than 305.86 °C when losing 10% weight under nitrogen. The cyclic voltammetry (CV) measurement and the electrochemical band gaps (Eg) of these copolymers are found below 2.00 ev.Keywords: Oxadiazole, Copolymer, Azo, Monomer, Thermal Properties, Electrical Properties.